Liberal Feminism’s Representative of Visual Signs in Katy Perry’s Music Video “Dark Horse” - Aprilia Nur Diana; Murni Fidiyanti (Journey: Journal of English Language and Pedagogy, 2023)
Liberal feminism, a prominent faction within the feminist movement, advocates gender equality, individual freedom, and women's rights. Modern artistic works, notably music videos, often act as implicit visual manifestos for promoting these ideals. This study aimed to analyze visual signs representing liberal feminism in Katy Perry's "Dark Horse" music video and identify the predominant aspects of liberal feminism depicted in it. Employing a qualitative descriptive method, data was collected by downloading a music video and watching it repeatedly to find elements of visual signs in the form of screenshots. The data was then analyzed to reveal the meaning that represents liberal feminism using Charles Pierce's triangle of meaning, along with various liberal feminist theories, including those by Tong, Worell, Hanifah, et al. The results found 11 visual signs representing the dual objectives of liberal feminism—freedom, liberality, and individuality, as well as equal rights and opportunities in political and social contexts. The second goal, emphasizing equality of rights and opportunities, was particularly prominent. As a result, "Dark Horse" implied that women possess the capability and entitlement to attain parity with men in various facets of life, as their abilities are comparable, if not superior.